Detection of parasite-derived tRNA and rRNA fragments in the peripheral blood of mice experimentally infected with Leishmania donovani and Leishmania amazonensis using next-generation sequencing analysis. (April 2023) - Kusakisako, Kodai; Nakao, Ryo; Katakura, Ken
Abstract: All prokaryotes and eukaryotes, including parasites, release extracellular vesicles or exosomes that contain selected proteins, lipids, nucleic acids, glycoconjugates, and metabolites. Leishmania exosomes are highly enriched in small RNAs derived from the rRNAs and tRNAs of the protozoan parasite species. Here, using plasma exosomes isolated by a kit and next-generation sequencing, we report the detection of fragments of parasite-derived rRNAs and tRNAs in the peripheral plasma samples of mice experimentally infected with Leishmania donovani and Leishmania amazonensis, the causative agents of Old World visceral leishmaniasis and New World disseminated cutaneous leishmaniasis, respectively. Detected RNA molecules of 28S rRNA, 5.8S rRNA, tRNA-Glu, and tRNA-Thr were common to both plasma samples of mice inoculated with L. donovani and L. amazonensis, whereas tRNA-Ile and tRNA-Trp were only detected in L. amazonensis -infected mice. The detected rRNAs and tRNA isotypes were matched with the exosomal components reported in a previous key study. Our preliminary results suggested that parasite-derived small RNAs were circulating in the blood of mice infected with Leishmania species, providing a better understanding of the roles of exosomal components in leishmaniasis and also new insights into exosome-based biomarkers for Leishmania infection. Graphical abstract: Detection of parasite-derived rRNAs and tRNA isotypes in the peripheral blood of mice experimentally infected with Leishmania donovani and Leishmania amazonensis. Unlabelled Image Highlights: We conducted NGS analysis of putative exosomes in the blood of murine leishmaniasis models. Parasite-derived 28S rRNA, 5.8S rRNA, tRNA-Glu, and tRNA-Thr were detected in both visceral and cutaneous models. Parasite-derived tRNA-Ile and tRNA-Trp were found in the plasma from the cutaneous model. The results provide new insights into exosome-based biomarkers for Leishmania infection.